USING THE PEDAGOGICAL CREATION OF ABDULLA AVLANI IN FORMING THE MORAL QUALITIES OF PRIMARY CLASS STUDENTS - A. Hayitov; S. Azizova (European International Journal of Pedagogics, 2023)
Тhis article is about the use of pedagogical activity, creativity and views of Abdullah Avlani in the formation of moral qualities, characteristics and worldview of our primary school students